INFLUENCE OF GENDER, LOCATION, AND PARENTAL FACTORS ON CAREER CHOICE OF SENIOR SECONDARY SCHOOL STUDENTS - Obiunu, Jude J.; Emakpor, Edmund E. (Advances in Social Sciences Research Journal, 2020)
The study investigated the influence of gender, location and parental factors on career choice of senior secondary school students in Delta and Edo States. Four research questions and four hypotheses guided the study. The study adopted an ex-post facto research design. A total of 1,200 students participated in the study. Multi-stage sampling procedure was used to draw the sample from the two states. A self-developed instrument was used for data collection. The instrument had a test-retest reliability coefficient of 0.64. The data obtained were analysed using chi-square (x2) statistics at 0.05 alpha level. The findings revealed that there was significant relationship between gender and career choice;and between socio-economic status of parents and career choice of senior secondary school students. The study, however, showed that there was no significant relationship between parental education and career choice; and between location of schools and career choice of senior secondary school students.